Manajemen Pengembangan Kurikulum Pendidikan Agama Islam di SDN 27 Bengkulu Selatan - Agung Wahyudin (JPT : Jurnal Pendidikan Tematik, 2024)
The Islamic Religious Education Curriculum has a very important position in shaping a person's personality. Islamic Religious Education educators as curriculum implementers combine the curriculum by prioritizing cognitive, affective and psychomotor aspects. The existence of this combined curriculum has an influence on the implementation of Islamic Religious Education curriculum management. This research aims to describe and analyze the implementation of Islamic Religious Education curriculum management, its effectiveness, and supporting and inhibiting factors that influence the implementation of Islamic Religious Education curriculum management at SDN 27 South Bengkulu.